Hydrocarbon chain length induces surface structure transitions in alkanethiolate-Au adatom self-assembled monolayers on Au(111) - Carro, Pilar (2013)
A detailed density functional calculation (DFT) study including van der Waals (vdW) dispersion forces of different adatom-containing models (RS−Auad−SR) at saturation coverage for methanethiol (MT), butanethiol (BT), and hexanethiol (HT) on Au(111) is presented. The stability analysis of these lattices shows a transition from the (3 × 4) to the c(4 × 2) surface structure when the number of C atoms in the alkanethiol chain is larger than 2, fairly predicting recent experimental observations for these systems. The transition takes place when the smaller energy needed to reconstruct the Au(111) surface and the larger binding energy for MT in the (3 × 4) MT lattice is compensated by a larger interaction energy between hydrocarbon chains in the c(4 × 2) lattice for BT and HT. Our calculations therefore explain why the (3 × 4) lattice is more stable for MT and ethanethiol (ET) while the c(4 × 2) lattice predominates for longer alkanethiols, thus shedding light on the behavior of alkanethiol self-assembled monolayers (SAMs) on Au(111).